Eszopiclone versus zopiclone in the treatment of insomnia (Clinics, 2016)
OBJECTIVE: To determine the therapeutic effects of two selective GABA-A agonists, zopiclone and eszopiclone, in the treatment of insomnia. METHODS: This study comprised a phase III, single-center, randomized, double-blind, double-dummy, parallel-group, non-inferiority trial. Patients were randomized to receive zopiclone 7.5 mg or eszopiclone 3 mg, both orally, for four weeks. In total, 199 patients were evaluated during two visits and then followed for at least six weeks. The primary endpoint was the Insomnia Severity Index after four weeks of treatment. Secondary endpoints were obtained through polysomnography data, including total sleep time, sleep latency and sleep efficiency. The frequency of adverse events was also analyzed. ClinicalTrials.gov: NCT01100164. RESULTS: The primary efficacy analysis demonstrated the non-inferiority of eszopiclone over zopiclone. Analysis of objective parameters assessed by polysomnography showed that eszopiclone increased total sleep time and also improved sleep efficiency. The safety profile of both study treatments was similar and the most common events reported in both groups were dysgeusia, headache, dizziness, irritability and nausea. Adverse events were observed in 223 patients, 109 (85.2%) in the eszopiclone group and 114 (87.7%) in the zopiclone group. CONCLUSION: Based on the Insomnia Severity Index at the end of four weeks of treatment, eszopiclone demonstrated efficacy comparable to that of zopiclone in the treatment of insomnia, increasing total sleep time as well as sleep efficiency according to polysomnography.